(untitled) (American Journal of Multidisciplinary Research and Innovation, 2025)
In this research, an effort was made to assess customer satisfaction with agricultural products in Helmand province and determine which marketing mix dimensions and factors significantly impact customer satisfaction. For data collection, 65 questionnaires were gathered from customers who had visited industrial production companies within the last three days. The collected data were later analysed using SPSS 26.0, OLS, and correlation techniques. The results show that Product has a positive relationship with customer satisfaction, Price has a positive relationship with customer satisfaction, Place has a positive relationship with customer satisfaction, Promotion has a positive relationship with customer satisfaction, Physical evidence has a positive relationship with customer satisfaction, People have a positive relationship with customer satisfaction, Process has a positive relationship with customer satisfaction. Based on the model, the obtained Adjusted R Square value was calculated, and if converted into a percentage, it is significant. Overall, the research findings indicate that all independent variables significantly impact the dependent variable, meaning that the independent variables contribute considerably to the changes in the dependent variable.